Reconception of Justice in the Intersection of Legal Protection and Victims' Rights in the Contemporary Criminal Justice System - Saiful Hamdi; Kalyana Surya Dewa, Gianina; Primasari, Lushiana (Kosmik Hukum, 2025)
Research on the protection of victims has been widely conducted, but the critical step of reconception of justice in the intersection of legal protection and victims' rights still leaves problems. This paper aims to examine the urgency of reconception of justice in the intersection of legal protection and victims' rights and see how the form of legal protection and victims' rights is viewed from the perspective of the contemporary criminal justice system. This research uses normative legal research, with secondary data consisting of primary and secondary legal materials relating to victims' rights, which are then analyzed using deductive syllogism analysis techniques. The results showed that justice for victims in the criminal justice system in Indonesia requires a reconstruction of the criminal law paradigm that is oriented towards the human rights of victims as protected subjects. This includes providing substantive space for victims to actively participate in the adjudication process, not just as witnesses or complementary evidence, but as the leading actors in restorative justice to achieve proper recovery. This reconception is expected to positively impact the justice system and increase social awareness of protecting victims' rights. The novelty in the 2023 Criminal Code, if integrated with related laws such as the Law on the Elimination of Domestic Violence, Law on Legal Aid, Law on Child Protection, Law on Witness and Victim Protection and Law on Criminal Acts of Sexual Violence, has the potential to shape a more equitable, transparent and responsive criminal justice system. The reconception of victim justice is not merely a change in norms, but a transformation towards social restorative justice that places victim protection at the core of modern criminal justice.